Within-subject biological variation of activated partial thromboplastin time, prothrombin time, fibrinogen, factor VIII and von Willebrand factor in pregnant women - Kristoffersen, Ann Helen; Petersen, Per Hyltoft; Bjørge, Line; Røraas, Thomas; Sandberg, Sverre (Clinical chemistry and laboratory medicine, 2018)
During pregnancy, interpretation of results from coagulation parameters can be difficult as the physiological changes that occur may affect the biochemical parameters. The aim of this study was to describe the normal course of five coagulation parameters in healthy pregnancies, and to estimate the within-subject biological variation (CVI). Blood samples were obtained every 4th week during pregnancy and three samples after delivery in 20 healthy women and every 4th week during a 40-week period in 19 healthy non-pregnant women. Activated partial thromboplastin time (APTT), prothrombin time (PT), PT International Normalized Ratio (INR), fibrinogen, factor VIII clot (FVIII:C) and von Willebrand factor antigen (vWF:Ag) were analyzed. The physiological changes during pregnancy were compensated by transformation into multiples of the median (MoM) and it is natural logarithm (lnMoM) in order to establish a kind of steady state, and CVI was calculated from the standard deviation. During pregnancy, APTT, PT and INR remained unchanged or decreased, depending upon the reagent used, while fibrinogen, FVIII:C and vWF:Ag increased gradually until delivery. The CVI in pregnancy were 2.2 and 3.0% for APTT, 2.3 and 2.6% for PT, 2.2 and 2.3% for INR, 7.2% for fibrinogen, 12.2% for FVIII:C and 11.3% for vWF:Ag, and corresponded with the CVI in non-pregnant women. Transformation of coagulation parameters in healthy pregnancies to MoM is a tool to establish a kind of steady state. Although there is a physiological change in these coagulation parameters during pregnancy, the CVI after lnMoM transformation was comparable with the CVI of non-pregnant women.